Nasofrontal encephalocele: A case report - Maria Isabel Ocampo-Navia; Isabella Lacouture-Silgado; Sara Henao-Romero; Andrés Méndez Gutiérrez; Juan Carlos Acevedo-González (Interdisciplinary Neurosurgery, 2023)
Encephaloceles are rare congenital anomalies resulting from neural tube defects, where abnormal openings of the skull permit the herniation of intracranial contents. This condition is uncommon in Western countries, but more prevalent in Southeast Asia and Africa. Frontoethmoidal encephaloceles account for approximately 20% of cases and encompass nasofrontal, nasoethmoidal and naso-orbital defects. Diagnosis and surgical planning entails performing neuroimages, and treatment requires a multidisciplinary team. Meticulous planning is necessary for surgery and timing is crucial to avoid complications. We report the rare case of a patient with a nasofrontal encephalocele, along with the diagnostic process and treatment with surgical repair.